Enhancing translation technology skills through blended learning: a study of student perceptions and satisfaction with bMOOC in higher education - Chan, Venus (Frontiers in Education, 2025)
The rapid advancement of translation technology and the increasing demand for professionals skilled in its application have highlighted the need for innovative and flexible pedagogies. Blended learning, which combines online and face-to-face components, has emerged as a promising method to address these educational needs. This exploratory study investigates students’ perceptions of the usefulness and satisfaction with a blended massive open online courses (MOOCs) approach for learning translation technology, which integrates MOOCs, online activities, guest talks, and on-site learning activities. Data were collected through questionnaires from a diverse group of 67 participants, including working adults as well as undergraduate and postgraduate students in Hong Kong. The quantitative analysis revealed that students held positive attitudes towards the integration of online components, such as MOOCs and live seminars, with face-to-face workshops. Participants were generally satisfied with the diverse learning activities and the range of topics covered by the bMOOC-TT approach. They perceived bMOOC-TT as both useful and effective. Specifically, the online learning components provided greater flexibility and autonomy, while the in-person activities facilitated hands-on practice of application of advanced translation software and more direct interaction. Additionally, the study found that younger learners tended to have more positive perceptions and acceptance of the bMOOC-TT approach.